Relevance between Proximal Humeral Migration and Rotator Cuff Tears - Zhang, Yichong; Chen, Jianhai; Ma, Mingtai; Ju, Jiabao; Jiang, Baoguo; Zhang, Peixun (Frontiers in Surgery, 2022)
Background Proximal humeral migration is common in patients with rotator cuff tear. In this study, we aimed to evaluate the relevance between proximal humeral migration and some rotator cuff tear related factors. Methods 75 patients with unilateral rotator cuff tear were retrospectively included from August 2016 to January 2018, who received MRI and X-ray before enrollment. We introduced Upward Migration Index (UMI) to stratify the patients into 3 groups, Group A: 1 < UMI ≤1.3, Group B: 1.3 < UMI≤ 1.4, and Group C: UMI > 1.4. Pearson correlation analysis and Logistic regression analysis were used to evaluate the relationship between UMI and age, sex, Body Mass Index (BMI), pain, fatty degeneration grade, tear size and thickness of ruptured tendon. Then chi-square test and Receiver Operator Characteristic Curve（ROC）were applied to measure the diagnostic value of UMI. Results The average UMI was 1.34±0.07, ranging from 1.16-1.48. For the Pearson correlation analysis, there was a negative correlation between UMI and tear size (R=-0.68, p＜0.01), also there was a negative correlation between UMI and VAS score (R=-0.342, p＜0.01). What’s more, there was a negative correlation between UMI and fatty degeneration grade (R=-0.373, p＜0.01). Ordinal multinomial logistic regression analysis indicated that tear size（β=-1.825, P＜0.001）was the independent predictor of UMI, which was a risk factor for humeral upward migration. 1.38 and 1.3 were the cut-off points of UMI to determine tears and distinguish large tears from small ones. Conclusions UMI is a good predictor for humeral upward migration, which is related to tear size of postero–superior cuff tears. When UMI is less than 1.3, a huge tear should be alerted. Combining physical examination and X-ray are helpful for evaluating rotator cuff tears.